2013
DOI: 10.1111/dom.12123
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of type 2 diabetes in the United Kingdom from 1991 to 2010

Abstract: There was a significant increase in the incidence of diagnosed type 2 diabetes between 1991 and 2010 and the proportion of people diagnosed at a relatively early age has increased markedly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
115
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 28 publications
11
115
0
1
Order By: Relevance
“…This finding suggests that either the incidence of RA has decreased more significantly, and is being masked by a change in disease classification criteria, or that physicians are slow to adapt to changes in nomenclature and classification systems. We do not believe that the reduction in the incidence of RA over time is due to the exclusion of previous incident cases, as this phenomenon would have resulted in a reduction in the incidence of other diseases such as gout [35] and type 2 diabetes for which the incidence in the CPRD has remained stable and risen, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that either the incidence of RA has decreased more significantly, and is being masked by a change in disease classification criteria, or that physicians are slow to adapt to changes in nomenclature and classification systems. We do not believe that the reduction in the incidence of RA over time is due to the exclusion of previous incident cases, as this phenomenon would have resulted in a reduction in the incidence of other diseases such as gout [35] and type 2 diabetes for which the incidence in the CPRD has remained stable and risen, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of type 2 diabetes in this population is higher than several rates reported around the globe. Considering studies which reported whole population data without splitting by sex, the pooled incidence rate of diabetes was reported to be 9.6 per 1000 person-years in Japan [20], 7.6 per 1000 person-years in the Bruneck study of Italy [21], 10.8 per 1000 person-years in the Asturias Study of Spain [22] and 5.15 per 1000 population in the United Kingdom [23]; however, the reported incidence rate of diabetes in an urban normal glucose tolerant population of India was 20.2 per 1000 person years which is extremely higher than our population [24]. Indeed, as previously reported in TLGS, during 1999–2008, the prevalence of obesity increased 33 and 23% in men and women respectively, and abdominal obesity during this period showed an increase of 71% in men and 9% in women [10].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for our change in practice are related to published data suggesting an association between maternal BMI and birth defects and the association between a raised BMI and GDM. An increase in sedentary living, poor diet and obesity in the UK and USA has contributed to the increasing incidence of type 2 diabetes and with an earlier age of onset [28]. Associations have been made between maternal BMI at conception, pre gestational insulin resistance and an increased incidence of birth defects.…”
Section: Discussionmentioning
confidence: 99%